Different coordination modes of trans‐2‐{[(2‐methoxyphenyl)imino]methyl}phenoxide in rare‐earth complexes: influence of the metal cation radius and the number of ligands on steric congestion and ligand coordination modes. Issue 10 (13th September 2018) - Roitershtein, Dmitrii M.; Minashina, Kseniya I.; Minyaev, Mikhail E.; Ananyev, Ivan V.; Lyssenko, Konstantin A.; Tavtorkin, Alexander N.; Nifant'ev, Ilya E.
Abstract : Structures of 2‐{[(2‐methoxyphenyl)imino]methyl}phenoxide complexes of rare‐earth metals are controlled by steric congestion influenced by the rare‐earth ionic radius, leading to three different coordination modes of the ligand. Abstract : A simple and effective synthetic route to homo‐ and heteroleptic rare‐earth (Ln = Y, La and Nd) complexes with a tridentate Schiff base anion has been demonstrated using exchange reactions of rare‐earth chlorides with in‐situ ‐generated sodium ( E )‐2‐{[(2‐methoxyphenyl)imino]methyl}phenoxide in different molar ratios in absolute methanol. Five crystal structures have been determined and studied, namely tris(2‐{[(2‐methoxyphenyl)imino]methyl}phenolato‐κ 3 O 1, N, O 2 )lanthanum, [La(C14 H12 NO2 )3 ], (1 ), tris(2‐{[(2‐methoxyphenyl)imino]methyl}phenolato‐κ 3 O 1, N, O 2 )neodymium tetrahydrofuran disolvate, [La(C14 H12 NO2 )3 ]·2C4 H8 O, (2 )·2THF, tris(2‐{[(2‐methoxyphenyl)imino]methyl}phenolato)‐κ 3 O 1, N, O 2 ;κ 3 O 1, N, O 2 ;κ 2 N, O 1 ‐yttrium, [Y(C14 H12 NO2 )3 ], (3 ), dichlorido‐1κ Cl, 2κ Cl ‐μ‐methanolato‐1:2κ 2 O : O ‐methanol‐2κ O ‐(μ‐2‐{[(2‐methoxyphenyl)imino]methyl}phenolato‐1κ 3 O 1, N, O 2 :2κ O 1 )bis(2‐{[(2‐methoxyphenyl)imino]methyl}phenolato)‐1κ 3 O 1, N, O 2 ;2κ 3 O 1, N, O 2 ‐diyttrium–tetrahydrofuran–methanol (1/1/1), [Y2 (C14 H12 NO2 )3 (CH3 O)Cl2 (CH4 O)]·CH4 O·C4 H8 O, (4 )·MeOH·THF, and bis(μ‐2‐{[(2‐methoxyphenyl)imino]methyl}phenolato‐1κ 3 O 1, N, O 2 :2κ O 1 )bis(2‐{[(2‐methoxyphenyl)imino]methyl}phenolato‐2κ 3 O 1, N, O 2 )sodiumyttrium chloroform disolvate, [NaY(C14 H12 NO2 )4 ]·2CHCl3, (5 )·2CHCl3 . Structural peculiarities of homoleptic tris(iminophenoxide)s (1 )–(3 ), binuclear tris(iminophenoxide) (4 ) and homoleptic ate tetrakis(iminophenoxide) (5 ) are discussed. The nonflat Schiff base ligand displays μ2 ‐κ 3 O 1, N, O 2 :κ O 1 bridging, and κ 3 O 1, N, O 2 and κ 2 N, O 1 terminal coordination modes, depending on steric congestion, which in turn depends on the ionic radii of the rare‐earth metals and the number of coordinated ligands. It has been demonstrated that interligand dihedral angles of the phenoxide ligand are convenient for comparing steric hindrance in complexes. (4 )·MeOH has a flat Y2 O2 rhomboid core and exhibits both inter‐ and intramolecular MeO—H…Cl hydrogen bonding. Catalytic systems based on complexes (1 )–(3 ) and (5 ) have demonstrated medium catalytic performance in acrylonitrile polymerization, providing polyacrylonitrile samples with narrow polydispersity.